Comparison of physiological indices with body fat percentage among adolescents in Singapore - Sng, Yi Qian. (2013)
Background: Singapore has been implementing exercise interventions to reduce body fat percentages in school (Soon et al., 2008; Goh & Pang, 2012). Studies has shown that physical fitness has an inverse relationship with body fat percentage (Wedderkopp et al., 2003).